Interaction of Arg194Trp and Arg399Gln genotypes with the risk of radiation on cancer patients - HARRY NUGROHO EKO SURNIYANTORO; NASTITI RAHAJENG; YANTI LUSIYANTI; TUR RAHARDJO; DYAH ERAWATI; LINA CHORIDAH; WIGATI DHAMIYATI; SRI RETNA DWIDANARTI (Society for Indonesian Biodiversity, 2019)
Abstract. Surniyantoro HNE, Rahajeng N, Lusiyanti Y, Rahardjo T, Erawati D, Choridah L, Dhamiyati W, Dwidanarti SR. 2019. Interaction of Arg194Trp and Arg399Gln genotypes with the risk of radiation on cancer patients. Biodiversitas 20: 2128-2133. Two of the common single-nucleotide polymorphisms are X-ray repair cross-complementary group 1 on exon 6 (Arg194Trp) and exon 10 (Arg399Gln). The purpose of this study was to determine the interactions between Arg194Trp and Arg399Gln genotypes combination with the risk of radiation on cancer patients in Indonesia, linked to micronuclei frequency as a biomarker of DNA damage. This study consisted of 19 patients with various cancer as the case group and 37 non-cancer participants as the control group. The determination of Arg149Trp and Arg399Gln alleles were performed using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism. Micronuclei assay was performed using Cytokinesis-block micronuclei cytome assay. The results of our study showed that micronuclei frequency was very significantly higher in the cancer patients compared to controls (111.16 ± 76.24 versus 16.89 ± 9.72, p<0.0001). Patients with heterozygous mutant genotypes CT had a lower frequency of micronuclei than patients with normal CC genotypes (105.6 ± 80.97 versus 117.33 ± 74.97). Likewise, patients with mutant genotype AA had a lower frequency of micronuclei than patients with normal GG genotype (64 versus 129.71 ± 90.68). The genetic polymorphisms of Arg194Trp and Arg399Gln demonstrated an association with the level of DNA damage on cancer patients.